Implementation of Religious and Moral Values in Communication with Young Children - Grahmayanuri, Novria; Hasibuan, Purnama Sari; Cahaya, Anggi Nur; Sitorus, Nadrah; Jemati, Jemati (Institut Agama Islam Negeri Kediri, 2025)
Instilling religious and moral values ​​in early childhood has a crucial role in shaping their character and communication ethics in the future. Facts in our environment state that many communication behaviors do not reflect religious and moral values. This study aims to analyze the implementation of religious and moral values ​​in early childhood communication, as well as to identify supporting and inhibiting factors in the process. The research method uses qualitative descriptive with data collection techniques through observation, interviews, and documentation. The data analysis technique uses content analysis techniques, namely identifying themes or patterns that emerge and analyzing them with existing theories. The results of the study indicate that the implementation of religious and moral values ​​in early childhood communication has begun to be applied through the use of polite words, mutual respect, and the habit of saying hello. Teachers and the family environment are the main factors influencing the success of this habit. The obstacles that arise are limited parental involvement due to time constraints and inconsistent implementation of moral values ​​in children. These findings emphasize the importance of synergy between educational institutions, families, and the social environment in instilling religious and moral values ​​in early childhood in a sustainable manner.